New Bleeding Time Devices with Retractable Blades Evaluated in Children, Healthy Volunteers and Patients with Prolonged Bleeding Time - Lethagen, Stefan; Kling, stefan (Thrombosis and Haemostasis, 1993)
The Simplate II-R and the Simplate Paediatric, are two new Simplate bleeding time devices with retractable blades. In this study we compared the Simplate II-R with the Simplate II bleeding time and found a good correlation when performed by the same technician both in 30 healthy volunteers and in 7 patients with prolonged bleeding time. The same normal ranges may be applied for the Simplate II-R as for the Simplate II bleeding time. The Simplate II-R bleeding time was highly reproducible in healthy volunteers when performed by the same technician. We found no correlation between age and bleeding time, and no significant difference in bleeding time between males and females.We performed the Simplate Paediatric bleeding time test and calculated the normal ranges in 84 healthy children in 4 age groups: 3 days, 3 months, 1 year and 3–6 years of age. The Simplate Paediatric bleeding times were shorter in the children than the Simplate II-R bleeding times in the adults. We found no significant correlation between bleeding time and the inverse platelet count, and no significant difference in bleeding time between boys and girls. The retractable blades in the Simplate II-R and the Simplate Paediatric reduce the risk of accidental cuts. Both devices yield reproducible bleeding time measurements and can be used instead of older Simplate variants.